Toxicity, overload, and anxiety: predictors of turnover intention in higher education faculty - Pariyanti, Eka; Puspitasari, Maya (Enrichment : Journal of Management, 2025)
Toxic workplace environments, excessive role demands, and financial anxiety are growing challenges in higher education, undermining lecturers’ well-being and increasing turnover intention. These issues are particularly evident in private institutions, where limited resources and job insecurity often intensify stressors. This study examines the influence of toxic workplace environment and work-role overload on turnover intention among lecturers in private higher education institutions in Lampung, with financial anxiety tested as a moderating variable. A total of 120 questionnaires were distributed through online and offline approaches, and after data cleaning, 102 valid responses were analysed. Data were processed using SPSS 26, with descriptive statistics, reliability testing, and correlation analysis conducted as preliminary steps. All constructs demonstrated strong internal consistency, with Cronbach’s alpha values above 0.70. Results from Moderated Regression Analysis (MRA) revealed that toxic workplace environment (β = 0.34, p < 0.01) and work-role overload (β = 0.41, p < 0.001) had significant positive effects on turnover intention. Moreover, financial anxiety significantly moderated the relationship between toxic workplace environment and turnover intention (β = 0.28, p < 0.05). These findings underscore the importance of addressing workplace stressors and financial concerns to reduce turnover intention and support healthier, more sustainable academic environments